Gaslighting : recognize manipulative and emotionally abusive people-and break free - Sarkis, Stephanie (Da Capo Press, 2018)
Gaslighting is a technique of manipulating others to gain control, often practiced by those with personality disorders (including Narcissistic Personality Disorder, Antisocial Personality Disorder, and Borderline Personality Disorder). Whether it's a spouse, parent, coworker, or friend, gaslighters use a series of manipulation and distraction tactics to distort the truth--from lying, controlling, withholding, triangulation, and more--making their victims question their own reality. Dr. Sarkis delves into the psychology behind the phenomenon, devoting chapters to specific scenarios, such as gaslighting in dating, in relationships, at work, and in families. With warning signs and examples of the destructive consequences along with practical tips and strategies, Gaslighting will help anyone trapped in a manipulative relationship to break free and heal from this toxic behavior.